Show that each of these conditional statements is a tautology using logical equivalences.a) (𝑝 ∧ 𝑞) → 𝑝b) ¬𝑝 → (𝑝 → 𝑞)c) (𝑝 ∧ 𝑞) → (𝑝 → 𝑞)
Question
Show that each of these conditional statements is a tautology using logical equivalences.
a) (𝑝 ∧ 𝑞) → 𝑝
b) ¬𝑝 → (𝑝 → 𝑞)
c) (𝑝 ∧ 𝑞) → (𝑝 → 𝑞)
Solution
Sure, let's go through each of these conditional statements one by one:
a) (𝑝 ∧ 𝑞) → 𝑝
This statement can be rewritten using the logical equivalence of the conditional statement, which is ¬𝑝 ∨ 𝑞. So, (𝑝 ∧ 𝑞) → 𝑝 becomes ¬(𝑝 ∧ 𝑞) ∨ 𝑝.
Using De Morgan's law, ¬(𝑝 ∧ 𝑞) can be rewritten as ¬𝑝 ∨ ¬𝑞. So, ¬(𝑝 ∧ 𝑞) ∨ 𝑝 becomes (¬𝑝 ∨ ¬𝑞) ∨ 𝑝.
Using the associative law, we can rearrange this to ¬𝑝 ∨ (¬𝑞 ∨ 𝑝).
Finally, using the law of disjunction (which states that 𝑝 ∨ ¬𝑝 is always true), we can see that (¬𝑞 ∨ 𝑝) is always true, and therefore the entire statement is a tautology.
b) ¬𝑝 → (𝑝 → 𝑞)
This statement can be rewritten using the logical equivalence of the conditional statement, which is ¬𝑝 ∨ (𝑝 → 𝑞).
The inner conditional statement (𝑝 → 𝑞) can also be rewritten using the logical equivalence of the conditional statement, which gives us ¬𝑝 ∨ (¬𝑝 ∨ 𝑞).
Using the associative law, we can rearrange this to (¬𝑝 ∨ ¬𝑝) ∨ 𝑞.
Finally, using the law of idempotency (which states that 𝑝 ∨ 𝑝 is equivalent to 𝑝), we can simplify this to ¬𝑝 ∨ 𝑞.
Since ¬𝑝 ∨ 𝑞 is always true (because either 𝑝 is false, or 𝑝 is true and 𝑞 is true), the entire statement is a tautology.
c) (𝑝 ∧ 𝑞) → (𝑝 → 𝑞)
This statement can be rewritten using the logical equivalence of the conditional statement, which is ¬(𝑝 ∧ 𝑞) ∨ (𝑝 → 𝑞).
Using De Morgan's law, ¬(𝑝 ∧ 𝑞) can be rewritten as ¬𝑝 ∨ ¬𝑞. So, ¬(𝑝 ∧ 𝑞) ∨ (𝑝 → 𝑞) becomes (¬𝑝 ∨ ¬𝑞) ∨ (𝑝 → 𝑞).
The inner conditional statement (𝑝 → 𝑞) can also be rewritten using the logical equivalence of the conditional statement, which gives us (¬𝑝 ∨ ¬𝑞) ∨ (¬𝑝 ∨ 𝑞).
Using the associative law, we can rearrange this to ¬𝑝 ∨ (¬𝑞 ∨ (¬𝑝 ∨ 𝑞)).
Finally, using the law of disjunction (which states that 𝑝 ∨ ¬𝑝 is always true), we can see that (¬𝑞 ∨ (¬𝑝 ∨ 𝑞)) is always true, and therefore the entire statement is a tautology.
Similar Questions
Show that ¬(𝑝 ∨ (¬𝑝 ∧ 𝑞)) and ¬𝑝 ∧ ¬𝑞 are logically equivalent by:a) Using a truth table (3 POINTS)b) Using logical equivalences
Using laws of logic prove that following are equivalenti)~ ( ) and ~ p q p q →
Which of the following propositions is a tautology0/1p ∧ ¬𝑝p ∨ 𝑝 (p ∧ ¬𝑝) ∨ (p ∨ ¬𝑝)(p ∨ ¬𝑝) → (p ∧ ¬𝑝)
Using Boolean laws simplify each of the following propositions:a. a ∧ b ∨ a ∧ ¬b
What are the truth values of these statements? a) ∃!xP(x)→∃xP(x) b) ∀x P(x) → ∃!xP(x) c) ∃!x¬P(x)→¬∀xP(x)
Upgrade your grade with Knowee
Get personalized homework help. Review tough concepts in more detail, or go deeper into your topic by exploring other relevant questions.